2021
DOI: 10.21873/anticanres.14922
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Impact of Prognostic Nutritional Index on Pembrolizumab for Metastatic Urothelial Carcinoma Resistant to Platinum-based Chemotherapy

Abstract: Background/Aim: We investigated the prognostic nutritional index (PNI), comprised of lymphocytes and albumin, as a potential prognosticator of metastatic urothelial carcinoma (mUC) patients receiving pembrolizumab. Patients and Methods: Sixty-five patients were retrospectively enrolled and classified as low (<40) and high (≥40) based on pretreatment PNI. Progression-free survival (PFS), overall survival (OS) and response rates were evaluated. Results: In the low PNI group, significantly shorter PFS and OS were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…In addition to high pretreatment level of NLR and CRP, percentage changes in these levels after initiation of pembrolizumab treatment were also significantly associated with OS in one study each [ 42 , 46 ]. UTUC [ 40 ] and smoking history/exposure [ 37 , 43 ] as pretreatment patients’ characteristics were significantly associated with OS. As for systemic nutritional condition, Geriatric Nutritional Risk Index [ 35 ]: a nutritional assessment tool defined by serum albumin levels and the ratio of actual to ideal body weight, Prognostic Nutritional Index[ 40 ]: a prognostic model comprising serum lymphocyte counts and albumin, and sarcopenia[ 45 ] were all significantly associated with OS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to high pretreatment level of NLR and CRP, percentage changes in these levels after initiation of pembrolizumab treatment were also significantly associated with OS in one study each [ 42 , 46 ]. UTUC [ 40 ] and smoking history/exposure [ 37 , 43 ] as pretreatment patients’ characteristics were significantly associated with OS. As for systemic nutritional condition, Geriatric Nutritional Risk Index [ 35 ]: a nutritional assessment tool defined by serum albumin levels and the ratio of actual to ideal body weight, Prognostic Nutritional Index[ 40 ]: a prognostic model comprising serum lymphocyte counts and albumin, and sarcopenia[ 45 ] were all significantly associated with OS.…”
Section: Resultsmentioning
confidence: 99%
“…After screening the titles and abstracts, a full-text review was performed for 42 articles. Finally, we identified 13 studies comprising 1311 patients treated with pembrolizumab for cisplatin-refractory metastatic UCs according to our inclusion criteria [35][36][37][38][39][40][41][42][43][44][45][46][47]. The characteristics of included patients and the outcomes are shown in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“… 11 Thus, there is increasing evidence that the PNI can be an effective prognostic marker, as well as a predictive indicator related to ICIs for various solid tumors. 12 13 14 Accordingly, this study investigated the clinical significance of the PNI for predicting the therapeutic effects of AGC patients with peritoneal metastases treated nivolumab monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, favorable ORR, PFS, and OS were observed in patients who had a CRP flare response. Recently, various biomarkers including blood cell count markers (11) or nutritional status-based markers such as prognostic nutritional index (12) were reported in pembrolizumab therapy for patients with advanced UC. Several studies on UC have reported that elevated CRP levels before surgery (13), chemotherapy (14,15), or ICIs treatment (3,7,8) were associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%